Caracterización epidemiológica y clínica del virus de papiloma humano en estudiantes de la Facultad de Ciencias de la Salud. - Lata Centeno, Lizbeth Carolina (2024)
The human papillomavirus (HPV) is a viral infection that is easily transmitted through skin contact during sexual activity. It commonly causes cellular changes in the squamous epithelium of the cervix. The aim of this study was to evaluate the epidemiological and clinical characteristics of the students from the Faculty of Health Sciences at the National University of Chimborazo regarding the situation of infection with this virus. The formula for calculating a finite population was applied with 1,939 students using a convenience sampling method. Exclusion criteria were applied to the sample. The information was based on the data collected, the focused epidemiological characteristics analyzed were age, number of pregnancies, last menstruation date, contraceptive methods, number of sexual partners, and the last Pap test date; In the clinics, cytological lesions were associated with the presence of itching, frequent vaginal infections, and the appearance of the cervix. The prevalence of HPV was 17.74%. The analysis showed a value of X² = 111.89, where a significant relationship was found between the cytology results for the virus and the clinical manifestations. These findings suggest that the population has a significant prevalence of infection, especially with high-risk oncogenic genotypes such as 18, 31, 33, and the relationship between the appearance of the cervix and infections by microorganisms that result in abnormal cytology findings.